Anacardato de cálcio e suas associações com ácido cítrico na alimentação de poedeiras comerciais - Watanabe, Germana Costa Aguiar (2021)
The objective was to evaluate the effect of the inclusion of calcium anacardate (ANC) associated or not with citric acid (CA) in the diet of laying hens on performance, internal and external quality of fresh eggs, serum biochemical profile, serum lipid peroxidation and yolks as well as enzymatic activity and lipid peroxidation of the liver and tissues of the reproductive system (ovary, magnum and uterus). For this, two experiments were carried out using 432 laying hens with an average weight of (1450 ± 100g) of the commercial strain Hy-Line W-36 in the period from 63 to 75 weeks of age. Distributed in a completely randomized design with nine treatments and six replications. The treatments consisted of: T1 – ration without addition of antioxidant; T2 – ration with the addition of 0.25% of ANC; T3 – diet with 0.25% ANC associated with 0.25% AC; T4 – ration with 0.50% of ANC; T5 – diet with 0.50% ANC associated with 0.25% AC; T6 – diet with 0.50% ANC associated with 0.50% AC; T7 – ration with 0.75% of ANC; T8 – diet with 0.75% ANC associated with 0.25% AC; T9 – diet with 0.75% ANC associated with 0.50% AC. There was no significant effect of treatments on laying hens performance, pH, relative weight of the gastrointestinal tract; gizzard; liver and reproductive system, percentage of yolk, albumen and shell, specific gravity, Haugh units, shell thickness, Cr, ALT, AST, COL.Total and TAG. However, treatments with 0.75% ANC and its association with AC (0.25 and 0.50) showed an increase in bud pigmentation. For the values of lipid oxidation of the yolks, the birds that received isolated doses of ANC (0.50% and 0.75%) presented lower oxidation, whereas the birds that received feed without the addition of antioxidants; 0.25% ANC; 0.50% of ANC + 0.25% of AC and 0.75% of ANC + 0.25% of AC showed a pro-oxidant effect. Even lower concentrations of Malonaldehyde (MDA) were observed in the blood serum of birds that consumed rations with an isolated dose of ANC (0.75 and 0.50%) and associated with 0.50% of AC. For enzymatic activity in the organs, there was a significant effect of the treatments on the liver and magnum CAT variables. Where birds that received isolated doses of ACN (0.50 and 0.75) and associations with AC at doses of (0.25 and 0.50) have lower enzymatic activity in the liver and higher enzymatic activity in the magnum. For SOD, there was a significant effect of treatments on the ovary, magnum and uterus tissues, the enzymatic activity in the ovary showed higher values for birds fed with ration without addition of antioxidant and 0.25% of ANC and lower oxidation for birds who consumed rations containing 0.50% of ANC associated with AC (0.25 and 0.50%) and 0.75% of ANC associated with AC (0.25 and 0.50%). In the magnum and uterus, birds that consumed feed without the addition of antioxidants had higher SOD values. In this way, the use of isolated doses of ANC or associated with AC can be added to the diet of laying hens up to the level of 0.75%, without changes in performance, egg quality and serum biochemistry in the period from 63 to 75 weeks old. However, the antioxidant activity in the tissues of the liver and reproductive system and the quality of the eggs can be improved with the lipid reduction of the yolks when isolated doses of ANC (0.50 and 0.75) are added to the diets or if the objective is to pigmentation of the yolks, the use of 0.75% ANC is recommended.